A Malay Language-Based Visual Programming Environment for Personal Digital Assistant - Anuar, Sazly (2007)
The research in the field of Visual Programming Language (VPL) is becoming more popular with the increase of computer speed and the graphics capabilities in recent years. A VPL programmer creates a program by connecting a picture or icon that will produce a directed graph, which will show the flow of the program in Visual Programming Environment (VPE). Since the number of today programmers as well as Personal Digital Assistant (PDA) users is rapidly increasing, it seems natural to create a VPE for the PDA. However, most of the programming environments developed for programming directly on PDA are classical textual programming. Another issue in VPE research is lack of concern on graph visualization. Most of the time, the graph layout is disorganized, hence causes difficulties for the user to understand the flow of the graph or program. Moreover, the small screen size of PDA has also becoming one of the main constraint factors. This research proposes the first Malay language-based VPE on PDA. The syntax and the semantics of visual environment are grammatically designed based on the visual programming. Graph grammar approach is used to describe the syntax for each component. Optimizing the graph layout is another main concern in this research. The hierarchical layout technique is used to optimize the graph produced, so that it can suit on limited size of the PDA screen. It is used because it has proved as the best way in arranging nodes and edges of a graph that will show the flow of the program. Two experiments were carried out in this research. First is the testing on MaVi Environment, which is done to prove that it can be executed on PDA and produces expected output. Second is the graph layout aesthetics testing, which is done to prove that the optimization of graph layout makes it more organized compared to the original graph layout. Both testing yield promising result and thus prove the objectives of the research have been achieved.